Respuesta :
Hey there!
m^(2)n + 2m^3
= -0.2^(2)(-9.6) + 2(-0.2)^3
= (-0.04)(-9.6) + 2(-0.3)^3
= 0.384 + 2(-0.008)
= 0.384 - 0.016
= 0.368
Therefore, your answer is: 0.368
Good luck on your assignment and enjoy your day!
~Amphitrite1040:)
[tex]\huge{\purple{\underline{\underline{\bf{\pink{ANSWER:-}}}}}}[/tex]
[tex]\implies\tt{ {m}^{2n} + {2m}^{3} } \\ \\ \implies\tt{ { - 0.02}^{ 2 \times - 9.6} + 2 {( - 0.02)}^{3} } \\ \\ \implies\tt{ - 0.04 \times - 9.6 + 2( - 0.0008)} \\ \\ \implies\tt{0.384 - 0.016} \\ \\ \implies\tt{0.368}[/tex]